Comparative archaeology reveals recurrent but nondeterministic pathways through complexification - Christian E. Peterson; C. Adam Berrey; Robert D. Drennan (Proceedings of the National Academy of Sciences, 2026)
The amount of variation observed among early complex societies has challenged efforts to understand their social dynamics. We advocate for a comparative approach that directly investigates the forces producing this variation. By holistically ranking 63 trajectories of societal change along five axes of differentiation, we characterize their development from a multidimensional perspective. Our analysis reveals that the majority of these trajectories align with one of six recurrent pathways through “complexification,” identified from broadly similar courses of development shared across multiple trajectories. These patterns provide a framework for understanding the conditions under which different forms of complexity emerged—or failed to do so. Particular attention is paid to the ways in which social and demographic forces interact along these pathways. Crucially, these forces interact probabilistically rather than deterministically, producing widespread tendencies rather than inevitable outcomes. Focusing future research on mediating and confounding variables, expanding the sample of trajectories available for analysis, identifying additional complexification pathways and the social forces at work in them, and leveraging the explanatory potential of trajectories that do not align well with any developmental pattern, will further enrich our understanding of the complexification process.